Chikungunya fever presenting with protracted severe pruritus. (2016) - Cunha, Burke A.; Leonichev, Victoria B.; Raza, Muhammad
Abstract: Travelers returning from the tropics often present with rash/fever. Those with rash/fever and myalgias/arthralgias are most likely due to chikungunya fever, dengue fever, or Zika virus. In these arthropod viral transmitted infections, the rash may be pruritic. The case presented here is that of chikungunya fever remarkable for the intensity and duration of her pruritis.